Increased working hours, simulation technology or competency based progression? What is the solution for surgical training?. Issue 8 (August 2017) - Sheikh, Zain
Abstract: Surgical training has changed in recent years. Surgical-skill training is considered suboptimal as early as medical school. Changes to medical team structure and societal demographics have also negatively impacted training. To counteract this, the following options are explored: (i) working hours; (ii) competency-based assessment (CBT); and (iii) surgical simulation. With the current requirement of service provision in the health service and political pressures, increasing working hours is not feasible. All stages of training are saturated with CBT. Increasing its use may be unwise, however adjusting it to further emphasize surgical skill may be beneficial. Whilst simulation is not a new concept in surgery, technological advancements have resulted in increased accessibility of computer based simulators. These have been shown to improve surgical skill so should be considered. Surgical training requires reform and trainees need to be involved from the outset. CBT should increase surgical emphasis and simulation should be assessed for integration into training.